Decarbonylation: A metabolic pathway of cannabidiol in humans. Issue 7 (20th March 2019) - Kraemer, Michael; Broecker, Sebastian; Madea, Burkhard; Hess, Cornelius
Abstract: Cannabidiol (CBD) is a non‐psychoactive cannabinoid, which is of growing medical interest. Previous studies on the metabolism of CBD showed mainly the formation of hydroxylated or oxidized derivatives, the formation of carboxylic acids or modifications of the aliphatic side chain. Using incubation of CBD with hepatic microsomes of mice, the formation of carbon monoxide was reported. We investigated the phase I metabolism of CBD and cannabidivarin (CBDV) using in vitro experiments with human liver microsomes in order to discover so far not considered metabolites. Identification of metabolites was done by liquid chromatography coupled with quadrupole time of flight mass spectrometry (LC−QToF−MS). Within these experiments, we came across decarbonylation of CBD and CBDV. Further investigations were focused on observed decarbonylated CBD (DCBD). To confirm this metabolite in humans in vivo, plasma samples containing large amounts of cannabinoids as well as serum and urine samples, collected after a voluntary intake of a CBD‐containing food supplement, were analyzed by LC coupled to triple quadrupole mass spectrometry (LC−QQQ−MS). DCBD was detected in in vitro incubation mixtures, serum samples, and urine samples (after alkaline or enzymatic hydrolysis) collected after the voluntary intake, as well as in plasma samples of cannabis users. DCBD appears to be an important supplementary human metabolite that might be helpful for the analytical confirmation of a CBD uptake and might improve the interpretation of the consumption of CBD‐containing products. Results of this study indicate a prolonged detectability of DCBD (in serum) in comparison to CBD after oral CBD ingestion. Abstract : Decarbonylated cannabidiol (DCBD) could be detected during in vitro investigations using human liver microsomes. The presence of this metabolite in vivo was confirmed analyzing plasma samples containing large amounts of cannabinoids as well as serum and urine samples, collected after a voluntary intake of a CBD‐containing food supplement. DCBD appears to be an important supplementary human metabolite that might be helpful for the analytical confirmation and interpretation of a CBD uptake.